Plant beneficial rhizobacteria community structure changes through developmental stages of peanut and maize - Anzuay, María Soledad; Pin Viso, Natalia Daniela; Ludueña, Liliana Mercedes; Morla, Federico Daniel; Angelini, Jorge Guillermo; Taurian, Tania (Elsevier, 2021)
Our objective in this study was to analyze the structure of the rhizobacterial community during different growth stages of peanut and maize plants. Microcosm assays were performed using pots containing unsterile soil from the peanut growing area of Argentina in which peanut and maize plants were grown during 120 and 100 days, respectively. Four to five samples of rhizospheric soil were obtained at the beginning of the assay, at an early growth stage of each plant and at the end of the assay. Two replicate DNA extractions from rhizospheric soil samples were realized per treatment on both microcosm assays to analyze rhizobacterial community structure by high-throughput sequencing of 16S rRNA gene. We observed changes in rhizobacteria community structure with crop developmental stages. Community structure changes occurred at several bacteria taxonomic levels, and major changes were observed in later stages. In particular, plant growth promoting bacteria genera were promoted in later stages. Our results indicate plant rhizospheric selection for growth enhancing rhizobacteria during stages of high nutrient demand. In conclusion, the structure of the rhizobacterial communities of peanut and maize are influenced by plant phenological stages, and beneficial bacteria are favoured in late phenological stages.